Implementation of the Use Of ICT Technology for Cognitive Assessment in Islamic Education Learning at the Elementary School - Khotib Al Chariz, Ahmad; Tubagus Idris M, Muhammad; Kumalasari, Dewi; Azizah, Nur; Habibah, Olivia (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2023)
The benefits of Information and Communication Technology (ICT) have expanded significantly in the field of education, aiding in filling gaps and enhancing teacher efficiency in the teaching and learning process to achieve educational goals. The utilization of ICT by educational institutions, particularly teachers, encompasses various aspects, one of which is facilitating the assessment or evaluation of students' cognitive domains. This study focuses on the utilization of ICT as an instrument in assessing the cognitive domains of students in Islamic Religious Education (PAI) classes. The research methodology employed is field research with a qualitative approach. In conducting qualitative analysis, this study utilizes a taxonomy-based analysis model that focuses on the domain and a single common characteristic. The model analyzes interview results with respondents, along with observations and field documentation. Data collection techniques involve interviews, observations, and documentation. The research findings indicate that PAI teachers at SD Negeri 01 Windurojo have implemented three cognitive domain assessment techniques during online learning, namely written tests, oral tests, and assignments. In their assessment processes, teachers make use of various ICT platforms such as Google Form, WhatsApp, and Google Meet.